KEDUDUKAN WALI ANAK DIBAWAH UMUR TERHADAP HARTA WARISAN MENURUT HUKUM ISLAM - Abdul Hakim; Risdalina Risdalina; Elviana Sagala (Jurnal Ilmiah Advokasi, 2020)
This study aims to analyze the legal basis for a child who is not yet 18 years old or has never been married in terms of the management of his inheritance by a guardian. Minors who have been married by law are called adults, even though they are not yet 18 years old. So in this case the authors will discuss about minors who have never been married so as not to be a different interpretation. Minors if both parents or one of their parents dies, it is an heir who has the right to the inheritance of the deceased parents. And for these assets are needed guardians to take care of the rights of minors to be used for children's needs both the survival needs of children and education and other needs. The guardian who handles the child's property is identical is the parent who lives the longest, or if both parents have died then there must be a guardian who is appointed by the Court based on a court decision. The future of a child can be threatened if a guardian makes use of his position by manipulating the transfer of the child's property, therefore the authors want to make this journal so that it can be known what exactly the guardian is, because many do not understand the benefits of a guardian for a minor. In the Compilation of Islamic Law mentioned in article 107 KHI guardianship only against children who have not reached the age of 21 years and or have never entered into a marriage. Trusteeship includes trusteeship of themselves and their assets. If the guardian is unable to act or neglects to carry out his guardianship duties, then the Religious Court can appoint one of the relatives to act as guardian at the request of the relative for a Muslim. Whereas in Marriage Law No. 16 of 2019 concerning amendments to Law Number 1 of 1974 concerning Marriage in article 50 it is mentioned that children have not reached the age of 18 (eighteen) years or have never entered into a marriage, which is not under the authority of parents, under the authority of the guardian.Â Keywords : Guardians of Minors, Inheritance, Islamic Law.